Development Of Batik Mangrove As A Community Empowerment Effort In The Banyuurip Village Ujung Pangkah Gresik - Ummu Aliyah; Mohamad Hariyadi; Prihadi Prihadi (OJS Universitas Muhammadiyah Gresik, 2020)
Fishing group Tirta Buana, around the beach of Banyuurip village, Ujung-Gresik. Cooperate with FERTILIZER and PT. PGN SAKA is Limited to hold the center of seedlings and mangrove sales. Until then from this mangrove business make a new tourist destination called Banyuurip Mangrove Center (BMC). Mangrove Banyuurip Ujungsemini lately visited by many domestic tourists. It is located about 35 kilometers from the city of Surabaya or about 23 kilometers from the city of Gresik to the north. The average day of visitors who come 600 people, but at the time of the feast can reach 1,600 visitors. The large number of tourists who come to enjoy the beautiful panorama of Mangrove if handled precisely will bring their source of income for the community Banyu Urip, the tip of the step has not been optimally absorbed. Several business opportunities will be directed in this Community Partnership program which includes: the empowerment of mangrove crops such as batik handicrafts made from mangrove, dodol mangrove and syrup made from mangrove. Seafood products are also the potential for the development of the production of the main shells. Besides the improvement of the facilities and Preasarana mangrove forest itself needs to be beautified so that visitors energy comfortable and feel at home in enjoying tourism of the BMC Mangrove such as The Making of jogging track to the shore of white sand, Gazebo level that So that tourists can see mangrove forests from above as well as repair and illumination of the road to access tourist attractions.